Homozygosity predominantly affects hypertrophic cardiomyopathy minor genes in an Egyptian clinical cohort. (3rd October 2022) - Allouba, M; Walsh, R; Afify, A; Halawa, S; Galal, A; Hosny, M; Fathy, M; Theotokis, P; Whiffin, N; Anwar, S; Elguindy, A; Ware, J; et al.
Abstract: Background: Consanguinity is prevalent in Egypt (35%) resulting in a high incidence of homozygosity. The influence of homozygosity on the genetics of Hypertrophic Cardiomyopathy (HCM) has not been adequately studied. Purpose: The purpose of this study is to define the genetic architecture of HCM in Egypt using ethnically-matched case and control cohorts. Methods: Prospective Egyptian patients (n=514) and controls (n=400) were recruited to Aswan Heart Centre for clinical phenotyping and genetic testing for 174 genes implicated in inherited cardiac conditions (Illumina). Rare variation (gnomAD filtering allele frequency ≤4x10–5) in 13 validated HCM genes were classified according to the American College of Medical Genetics (ACMG) guidelines and compared with a prospective HCM cohort of predominantly European ancestry (n=684). Results: Significantly fewer rare variants detected in Egyptian patients could be classified as (likely) pathogenic compared to Europeans (40.8% vs. 61.6%, p-value=1.6x10–5). Incorporating analysis from these Egyptian case-control cohorts into the ACMG guidelines increased this yield to 53.8%. Homozygous variants were more frequently observed in Egyptian patients (4.1% vs 0.1%, p-value=2x10–7), with variants in the minor HCM genes MYL2, MYL3 and CSRP3 more likely to present in homozygosity than the major genes (MYH7, MYBPC3 and troponins), suggesting such variants are less penetrant in the heterozygous state. Conclusions: The integration of Egyptian-specific genetic and phenotypic data significantly improves variant interpretation in HCM and consequently the precision of genetic testing. The observed prevalence of homozygosity and rare variation in minor HCM genes in Egyptian patients provides important insights into its disease-mechanisms and genetics. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Science and Technology Development FundAl Alfi Foundation